THE EFFECT OF SURFACE MECHANICAL ACTIVATION OF INORGANIC PIGMENTS ON THE STABILITY OF THEIR AQUEOUS DISPERSIONS IN THE PRESENCE OF ETHYL HYDROXYETHYL CELLULOSE - Aleksandrova, Yulia; Budanova, Natalia; Zharova, Nelli; Okorokova, Nadezhda; Ustyuzhaninova, Galina; Farmakovskaya, Ariadna; Kohlert, Victoria (Revista Inclusiones, 2020)
The stability of aqueous dispersions of inorganic pigments TiO2 and Fe2O3 in the presence of a nontoxic water-soluble polymer (ethylhydroxyethyl cellulose) with two methods of mechanically activating the surface of the pigments processing them in a disintegrator and in ultrasound field was studied. If there is no polymer stabilizer, intense exposure to aqueous dispersions of pigments leads to their rapid coagulation. If there is ethylhydroxyethyl cellulose, a small stabilizing effect is observed, which is significantly enhanced when processing dispersions in a disintegrator and in an ultrasonic field. Moreover, the stability of pigment dispersions depends not very much on the method of mechanically activating their surface, but on the duration of intense exposure